AKULTURASI ISLAM DAN BUDAYA LOKAL (Memahami Nilai-Nilai Ritual Maulid Nabi di Pekalongan) - Nihayatur Rohmah (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2015)
Empirically, a religion can be seen from its followers behaviours in their daily life. The behaviors may become expression of religious sense which can be traced back from the values of religion that they believe. Such expression, later on, makes a religion exist as symbol of culture. This paper will explain about the sample of transformation and acculturation of java and Islam in the Islamic teachings. We shall explore the local wisdom about tradition celebration of the birth of prophet Muhammad in Pekalongan and it’s called muludan. In there are amount of rituals for celebrate of the birth of prophet.